Natural Killer cells and monoclonal antibodies: Two partners for successful antibody dependent cytotoxicity against tumor cells. (April 2021) - Gauthier, Mélanie; Laroye, Caroline; Bensoussan, Danièle; Boura, Cédric; Decot, Véronique
Graphical abstract: 1. Monoclonal antibodies targeting tumors are one of the most important discoveries in the field of cancer therapy in the last decade. 2. A lack of Natural Killer cells observed in many cancers may therefore be a cause of the low efficacy of antibodies observed in some clinical situations. 3. The ways to enhance the ADCC mechanism and the perspective of the treatment with therapeutic antibodies : enhancement of CD16 expression by cytokines or anti-CD137 antibody 4. A combination of NK cell adoptive immunotherapy and monoclonal antibodies may overcome the resistance to the treatment and enhance their efficacy. Highlights: Therapeutic antibodies are used to treat solid tumors and hematologic malignancies. A lack of Natural killer cells diminishes the antibody efficacy against the tumor. NK cells combined with antibodies can overcome a resistance to the antibody. Cytokine use or preventing CD16 shedding may potentialize the NK cell efficacy. Abstract: Monoclonal antibodies targeting tumors are one of the most important discoveries in the field of cancer. Although several effective antibodies have been developed, a relapse may occur. One of their mechanisms of action is Antibody Dependent Cell Cytotoxicity (ADCC), by engaging the Fc γ receptor CD16 expressing Natural Killer cells, innate lymphoid cells involved in cancer immunosurveillance and able to kill tumor cells. A lack of NK cells observed in many cancers may therefore be a cause of the low efficacy of antibodies observed in some clinical situations. Here we review clear evidences of the essential partnership between NK cells and antibodies showed in vitro, in vivo, and in clinical trials in different indications, describe the hurdles and ways to enhance ADCC and the evolution of monoclonal antibody therapy. NK cell adoptive immunotherapy combined with monoclonal antibodies may overcome the resistance to the treatment and enhance their efficacy.